Oral Azacitidine Maintenance Therapy for Acute Myeloid Leukemia in First Remission - Wei, A (2020)
Background: Although induction chemotherapy results in remission in many older patients with acute myeloid leukemia (AML), relapse is common and overall survival is poor. Methods: We conducted a phase 3, randomized, double-blind, placebo-controlled trial of the oral formulation of azacitidine (CC-486, a hypomethylating agent that is not bioequivalent to injectable azacitidine), as maintenance therapy in patients with AML who were in first remission after intensive chemotherapy. Patients who were 55 years of age or older, were in complete remission with or without complete blood count recovery, and were not candidates for hematopoietic stem-cell transplantation were randomly assigned to receive CC-486 (300 mg) or placebo once daily for 14 days per 28-day cycle. The primary end point was overall survival. Secondary end points included relapse-free survival and health-related quality of life. Results: A total of 472 patients underwent randomization; 238 were assigned to the CC-486 group and 234 were assigned to the placebo group. The median age was 68 years (range, 55 to 86). Median overall survival from the time of randomization was significantly longer with CC-486 than with placebo (24.7 months and 14.8 months, respectively; P<0.001). Median relapse-free survival was also significantly longer with CC-486 than with placebo (10.2 months and 4.8 months, respectively; P<0.001). Benefits of CC-486 with respect to overall and relapse-free survival were shown in most subgroups defined according to baseline characteristics. The most common adverse events in both groups were grade 1 or 2 gastrointestinal events. Common grade 3 or 4 adverse events were neutropenia (in 41% of patients in the CC-486 group and 24% of patients in the placebo group) and thrombocytopenia (in 22% and 21%, respectively). Overall health-related quality of life was preserved during CC-486 treatment. Conclusions: CC-486 maintenance therapy was associated with significantly longer overall and relapse-free survival than placebo among older patients with AML who were in remission after chemotherapy. Side effects were mainly gastrointestinal symptoms and neutropenia. Quality-of-life measures were maintained throughout treatment. (Supported by Celgene; QUAZAR AML-001 ClinicalTrials.gov number, NCT01757535.).